(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Education provides us the opportunity for holistic growth and development. It is an activity as well as a process which modifies the behaviour of a person from instinctive behaviour to human behaviour. It transforms our raw personality into refined personality. We start acting rationally instead of impulsively. It develops our thinking and reasoning power. It is responsible for the supply of good citizens who can contribute to the growth of the country. In all the stages of education right from nursery to university education, the senior secondary stage, is the most important stage, because, this stage provides the base for further education. In fact future depends on this stage. As progress of a nation depends upon its students’ academic performance. Therefore, every nation emphasizes academic performance. School phobia first let us see what is school phobia? phobia means apprehension, tension, or uneasiness characterized by fear, dread, or uncertainty about something the source of which is largely unknown or unrecognized by the individual It may consist in persistent apprehensions of future events as well as in generalized emotional reactions to any choice point or decision mentioned that School phobia disorders are defined by the dual characteristics of excessive emotional fear and physiologic hyper arousals. School phobia is one of the most widely experienced emotion and one of the most essential constructs of all human behaviour. It is a displeasing feeling of uneasiness, nervousness, apprehension, fear, concern or worry. In today’s cut throat competitive environment, school phobia is a common phenomenon of everyday life. It plays a crucial role in human life, because most of the individuals are the victims of fear in different ways.